The Complementarity of hunter and farmer roles as a strategy in the development of excellent Salespeople - de Almeida, César; Lima Santos, Leandro (Journal of Sustainable Competitive Intelligence, 2024)
Objective: This study aims to highlight the complementarity of Hunter and Farmer profiles for sales professionals, aligning performance with strategies that balance quality and customer retention. Method: The research is descriptive and quantitative, using a structured questionnaire applied via Google Forms. Data analysis was conducted using structural equation modeling. Results: Findings reveal that customer focus is crucial for sales performance, with Hunter and Farmer profiles becoming complementary as organizations mature. This leads to more skilled salespeople capable of addressing both basic and advanced client needs. Conclusion and Practical Implications: The study concludes that businesses should strategically develop sales professionals by integrating Hunter and Farmer skills, enhancing performance and customer service quality. Recruitment should consider this complementarity, especially in customer-focused strategies.